Implementation of Activity-Based Costing to Increase Profits for Traditional Treatment Providers - Munandar, Agus; Maratis, Jerry; Sugiyanto, Didik; Kadlina (PT Inovasi Pratama Internasional, 2024)
The growth of traditional medicine in Indonesia is so rapid. Traditional medicine serves as an alternative to modern medical treatment, particularly in areas that are difficult to access by modern healthcare services. This paper aims to describe the impact of activity based costing implementation on profitability of traditional treatment. The method for this research is comparative study between pre and post implementation of ABC. For that reason, the method used in this research is one group pretest-posttest design. The number of members in the group is 20 respondents. The results of this paper show that there is a significant difference in profit before and after ABC implementation.